The frequency of polymorphic variants of filaggrin gene and clinical atopic dermatitis - Filipowska-Grońska, Agata; Weryńska-Kalemba, Maria; Bożek, Andrzej; Filipowska, Barbara; Żebracka-Gala, Jadwiga; Rusinek, Dagmara; Kula, Dorota; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: As far as pathogenesis of the atopic dermatitis (AD) is concerned, the roles of an impaired epidermal barrier and cornified cell envelope are widely emphasized. Aim : The assessment of mutations of the filaggrin gene and their connection with the clinical picture of AD as well as selected allergological and environmental indicators. Material and methods: 105 patients with diagnosed AD on the basis of diagnostic criteria were included. For every patient of the examined group, quantitative determination of the total concentration of IgE and the concentration of IgE antibodies to selected allergens were examined. For all patients, studies were performed by means of analysis of two genomic gene variants of profilaggrin (FLG) – R501X and 2282del4. Results : Loss-of-function mutations in the filaggrin gene were shown in 12 (11.4%) patients in the examined group. All patients in the study group who developed one of the tested loss-of-function mutations in the filaggrin gene demonstrated an extrinsic, allergic form of atopic dermatitis. A significant association (p = 0.0002) between the presence of one of the tested loss-of-function mutations in the filaggrin gene and elevated levels of total concentration of immunoglobulin E was shown. Conclusions : Patients with AD of null mutations in the filaggrin gene demonstrate a relationship with the total and specific concentration of immunoglobulin E, specifically higher concentrations of IgE against aeroallergens and alimentary allergens as well as elevated levels of total immunoglobulin E.